Risk perception and intent to take precautionary actions against COVID-19 among adult population during pandemic in Nepal - Khanal, Shanti Prasad; Budhathoki, Chitra Bahadur; Acharya, Devaraj (Journal of Health Promotion, 2022)
This cross-sectional study sought whether there was an association between COVID-19 risk perception and the intention to take precautionary health measures among Nepalese adults aged 20 to 60 years. A multi-stage sampling technique was used to select study participants in this study. With the help of Kobo Toolbox application programs, field enumerators interviewed 1072 adults from 14 districts of Nepal in March and April of 2021. In the study, the average age of participants was 35.11 years. Over half (52%) of them were women, and 44% were the Brahmins and Chhetri caste. Apart from perceived susceptibility, the study showed that the largest group (41%) of respondents had the lowest level of perceived susceptibility. Only a few (14.8%) of respondents expressed a strong intention to take safe measures (M=1.14 ±0.35). The study results indicated that four constructs of the health belief model such as perceived severity, barriers, benefits, and self-efficacy were positively correlated (>0.05) with taking protective health measures. In contrast, perceived susceptibility was not associated (0.53) with the intention to take protective health measures. Overall, Nepalese people are reluctant to act against COVID-19 because of their low-risk perception, which makes it necessary to raise public awareness regarding COVID-19.